Polyphosphate-kinase-1 dependent polyphosphate hyperaccumulation for acclimation to nutrient loss in the cyanobacterium, Synechocystis sp. PCC 6803 - Sato, Norihiro; Endo, Mizuki; Nishi, Hiroki; Fujiwara, Shoko; Tsuzuki, Mikio (Frontiers in Plant Science, 2024)
Polyphosphate is prevalent in living organisms. To obtain insights into polyphosphate synthesis and its physiological significance in cyanobacteria, we characterize sll0290, a homolog of the polyphosphate-kinase-1 gene, in the freshwater cyanobacterium Synechocystis sp. PCC 6803. The Sll0290 protein structure reveals characteristics of Ppk1. A Synechocystis sll0290 disruptant and sll0290-overexpressing Escherichia coli transformant demonstrated loss and gain of polyphosphate synthesis ability, respectively. Accordingly, sll0290 is identified as ppk1. The disruptant (Δppk1) grows normally with aeration of ordinary air (0.04% CO2), consistent with its photosynthesis comparable to the wild type level, which contrasts with a previously reported high-CO2 (5%) requirement for Δppk1 in an alkaline hot spring cyanobacterium, Synechococcus OS-B’. Synechocystis Δppk1 is defective in polyphosphate hyperaccumulation and survival competence at the stationary phase, and also under sulfur-starvation conditions, implying that sulfur limitation is one of the triggers to induce polyphosphate hyperaccumulation in stationary cells. Furthermore, Δppk1 is defective in the enhancement of total phosphorus contents under sulfur-starvation conditions, a phenomenon that is only partially explained by polyphosphate hyperaccumulation. This study therefore demonstrates that in Synechocystis, ppk1 is not essential for low-CO2 acclimation but plays a crucial role in dynamic P-metabolic regulation, including polyP hyperaccumulation, to maintain physiological fitness under sulfur-starvation conditions.